STUDI ANALISIS TERHADAP NILAINILAI KESADARAN HUKUM DALAM PENDIDIKAN KEWARGANEGARAAN (CIVIC EDUCATION) DI PERGURUAN TINGGI ISLAM - John Kenedi (Jurnal Madania, 2015)
An Analysis Study on Sense of Justice in Civic Education in Islamic University. This article is aimed at describing the values of sense of justice used by Islamic Universities as the core of civic education subject. Its subject that considerably deals with human democracy, human right, and civil society has a lot of values of sense of justice will give possitive effect on many people. Nevertheles, based on the collected data, the history of civic education, and the fact of legal insecurity applied in social life, the subject of civic education recently has not been seemed to be good significant effect on the sense of justice in social life. Hence, it needs a concrete support from Islamic university by reviewing a comparison between a number of lecturers of civic education and their students. In addition, it also needs increasing number of SKS (-es) become three SKS (-es) in order that objective of the civic education material will be successfully implemented in reforming civil society have sense of justice.